Shover boy shoving cylinder into flattening oven (Underwood & Underwood)
View of a worker transferring a cylinder of glass into a flattening oven at an unidentified factory. This photograph is one of a set of seven stereographs detailing the production of glass sheets.
Keywords: Employees; Glass blowing and working; Manufacturing industries; Glass manufacture